The sensitivity of the alternative maximal accumulated oxygen deficit method to discriminate training status - Zagatto, Alessandro M. [UNESP]; Nakamura, Fabio Y.; Milioni, Fabio [UNESP]; Miyagi, Willian E. [UNESP]; de Poli, Rodrigo A. B. [UNESP]; Padulo, Johnny; Bragazzi, Nicola L.; Papoti, Marcelo (Taylor & Francis, 2017)
The purpose of the study was to investigate the sensitivity of an alternative maximal accumulated oxygen deficit (MAODALT) method to discriminate the “anaerobic” capacity while comparing: least trained (LT) participants (n = 12), moderately trained (MT) participants (n = 12), endurance trained (ET) participants (n = 16), and rugby (RG) players (n = 11). Participants underwent a graded exercise test on a treadmill and a supramaximal effort for assessing MAODALT. MAODALT was calculated as the sum of oxygen equivalents from the phosphagen and glycolytic metabolic pathways. MAODALT was significantly higher (P < 0.05) in RG (64.4 ± 12.1 mL · kg−1) than in ET (56.8 ± 5.4 mL · kg−1; effect size [ES] = 0.77; +13.5%), MT (53.8 ± 5.3 mL · kg−1; ES = 1.08; +19.8%), and LT (49.9 ± 4.5 mL · kg−1; ES = 1.50; +36.4%). In addition, the magnitude-based inference analysis revealed that MAODALT was likely (LT vs. MT), very likely (MT vs. RG, and ET vs. RG) and most likely (LT vs. ET, and LT vs. RG) different between all groups, except for MT and ET, which presented an unclear difference. In conclusion, MAODALT was sensitive enough to distinguish the “anaerobic” capacity in individuals with different training status, especially for RG players compared with LT participants and MT participants.
Keywords: blood lactate response; excessive post-exercise oxygen consumption; physical conditioning; “Anaerobic” capacity